Gaining and sustaining schistosomiasis control: study protocol and baseline data prior to different treatment strategies in five African countries. Issue 1 (December 2016) - Ezeamama, Amara; He, Chun-La; Shen, Ye; Yin, Xiao-Ping; Binder, Sue; Campbell, Carl; Rathbun, Stephen; Whalen, Christopher; N'Goran, Eliézer; Utzinger, Jürg; Olsen, Annette; Magnussen, Pascal; et al.
Abstract Background The Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) was established in 2008 to answer strategic questions about schistosomiasis control. For programme managers, a high-priority question is: what are the most cost-effective strategies for delivering preventive chemotherapy (PCT) with praziquantel (PZQ)? This paper describes the process SCORE used to transform this question into a harmonized research protocol, the study design for answering this question, the village eligibility assessments and data resulting from the first year of the study. Methods Beginning in 2009, SCORE held a series of meetings to specify empirical questions and design studies related to different schedules of PCT for schistosomiasis control in communities with high (gaining control studies) and moderate (sustaining control studies) prevalence ofSchistosoma infection among school-aged children. Seven studies are currently being implemented in five African countries. During the first year, villages were screened for eligibility, and data were collected on prevalence and intensity of infection prior to randomisation and the implementation of different schemes of PZQ intervention strategies. Results These studies of different treatment schedules with PZQ will provide the most comprehensive data thus far on the optimal frequency and continuity of PCT for schistosomiasis infection and morbidity control. Conclusions We expect that the study outcomes will provide data for decision-making for country programme managers and a rich resource of information to the schistosomiasis research community. Trial registration The trials are registered at International Standard Randomised Controlled Trial registry (identifiers:ISRCTN99401114, ISRCTN14849830, ISRCTN16755535, ISRCTN14117624, ISRCTN95819193 andISRCTN32045736 ).